Probing the dynamic self-assembly behaviour of photoswitchable wormlike micelles in real-time. Issue 6 (12th November 2018) - Kelly, Elaine A.; Houston, Judith E.; Evans, Rachel C.
Abstract : UV-Vis absorption spectroscopy is combined with small-angle neutron scattering to monitor the dynamic self-assembly of an azobenzene photosurfactant from worm-like micelles to fractals during photoisomerization. Abstract : Understanding the dynamic self-assembly behaviour of azobenzene photosurfactants (AzoPS) is crucial to advance their use in controlled release applications such as drug delivery and micellar catalysis. Currently, their behaviour in the equilibrium cis - and trans -photostationary states is more widely understood than during the photoisomerisation process itself. Here, we investigate the time-dependent self-assembly of the different photoisomers of a model neutral AzoPS, tetraethylene glycol mono(4′, 4-octyloxy, octyl-azobenzene) (C8 AzoOC8 E4 ) using small-angle neutron scattering (SANS). We show that the incorporation of in situ UV-Vis absorption spectroscopy with SANS allows the scattering profile, and hence micelle shape, to be correlated with the extent of photoisomerisation in real-time. It was observed that C8 AzoOC8 E4 could switch between wormlike micelles ( trans native state) and fractal aggregates (under UV light), with changes in the self-assembled structure arising concurrently with changes in the absorption spectrum. Wormlike micelles could be recovered within 60 seconds of blue light illumination. To the best of our knowledge, this is the first time the degree of AzoPS photoisomerisation has been tracked in situ through combined UV-Vis absorption spectroscopy-SANS measurements. This technique could be widely used to gain mechanistic and kinetic insights into light-dependent processes that are reliant on self-assembly.